Monetary Transmission and Financial Indexation : Evidence from the Chilean Economy. (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1994)
This paper reviews empirical evidence on the operation of the monetary transmission mechanism based on targeting of interest rates on indexed assets in the Chilean economy. The empirical evidence has two policy implications. First, interest rates on indexed assets do not fully reflect real interest rates because of imperfections of backward indexation magnified by the variability of monthly inflation. Second, while substantial adjustments to interest rates on indexed assets affect the cyclical position of output and inflation, there is no evidence of a stable, systematic relationship between these three variables. In contrast, money growth and unexpected inflation play a significant role in the transmission mechanism. This evidence calls for an eclectic approach to monetary policy. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.